A Study on Factors Influencing the Work Interference with Family and Family Interference with the Work of Selected Cement Industry Workers - Anu Baskar; Dr. A.Mohansundaram (International Journal of Engineering and Management Research, 2018)
Every individual plans his/her schedule for a day based on their work agenda. Things are not the same as they were before twenty five years. Quality of work life is something that each and every individual expects from their work in their life, from small job worker to a chief executive officer of a reputed organization. The benefits of quality of work life initiatives go to both employees and employers. The presence of quality of work life initiatives makes the employees feel safe, relatively well satisfied and provides them the opportunities to grow. Largely, it appears that the main concerns of an effective quality of work life program are improved working conditions mainly from the employee’s perspective and greater organizational effectiveness mainly from the employer’s perspective Considering how important quality of work life is for the employees as well as the employers, an attempt is made to measure the quality of work life measures in a leading and more vital sector in India which contributes significantly to the economical development of the country. Hence, the quality of work life and work life balance of cement industry workers the present study analyses factors influencing the work interference with family and family interference with the work of selected cement industry workers in selected industries.